On Cattaneo-Chrystov heat flux model for nanofluid flow on Darcy–Forchheimer porous medium past unsteady stretching cylinder - Sreedhar Sobhanapuram; S.V.V Rama Devi; Charankumar Ganteda; Rajyalakshmi Kottapalli; Vediyappan Govindan; Haewon Byeon; Busayamas Pimpunchat (International Journal of Thermofluids)
In a Darcy-Forchheimer porous medium with variable thermal conductivity, this work describes the convective transport mechanisms of Williamson nanofluid and nanofluid flow via an unstable stretched cylindrical sheet. The governing boundary evaluates issue of the flow regime is formulated utilizing the conservation laws of mass, momentum, energy. A couple of nonlinear partial differential constitutions are used to express the flow. A suitable similarity transformation along with certain approaches are applied to convert the pair of partial differential constitutions into an initial value problem system. In this analysis, the Cattaneo-Chrystov model is introduced. After that, the shooting strategy and the Runge-Kutta fourth order are used to numerically solve the system of initial value problems. Analysis is done on the effects of several factors on the nanofluid's temperature, velocity, and concentration contours. such as the thermal conductivity parameter, the concentration and temperature Biot numbers, the unsteady parameter, and others. Conversely, larger values of the unstable parameter result in significant wall friction that hinders the nanofluid'smobility. Furthermore, under widely accepted assumptions, the numerical approach found here shows great agreement with several previous efforts. An uplifting in the unsteady factor causes the nanofluid's temperature and concentration boundary layers to enlarge. When the corresponding Biot numbers (thermal and concentration) grow, the two boundary layers of the nanofluid expand, initiating the convective mass and heat transfers from the wall to the system. The rates of mass and heat transfers increase and decrease in tandem with increases in the thermal conductivity parameter and thermal Biot number, respectively; however, the transfers exhibit the opposite behavior for higher concentration Biot number values.Compared with the existing research, the outcomes demonstrate excellent congruence.